2008
DOI: 10.1080/10439460701718583
|View full text |Cite
|
Sign up to set email alerts
|

Building the capacity of police change agents: The nexus policing project

Abstract: and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae and drug doses should be independently v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 21 publications
4
43
0
Order By: Relevance
“…Indeed, researchers have long found that police officers have a high degree of distrust towards outsiders (e.g., citizens, academicians, lawyers, etc.) (Paoline, 2003;Wood, Fleming, & Marks, 2008). While it would have been optimal to have sociodemographics, time in service, and rank information on nonresponders so that they could be compared to respondents, such data were not available from the agencies since no identifying information were shared between agencies and the lead researcher.…”
Section: Data and Measuresmentioning
confidence: 98%
“…Indeed, researchers have long found that police officers have a high degree of distrust towards outsiders (e.g., citizens, academicians, lawyers, etc.) (Paoline, 2003;Wood, Fleming, & Marks, 2008). While it would have been optimal to have sociodemographics, time in service, and rank information on nonresponders so that they could be compared to respondents, such data were not available from the agencies since no identifying information were shared between agencies and the lead researcher.…”
Section: Data and Measuresmentioning
confidence: 98%
“…Reflecting on the formation of the International Network for Hate Crime Studies (INHS), Perry et al (2015) also point out that researchers, practitioners and policy makers have tended to work in silos, with little communication across the sectors. Recent publications from academics (Fleming, 2012;Wood et al 2008;Fyfe and Wilson, 2012) and police (Wilkinson, 2010) have focused on how to build effective collaborations between police and academics, for instance highlighting the benefits to be gleaned from participatory action research (Wood et al 2008).…”
Section: Policing Research and The Social Sciencesmentioning
confidence: 99%
“…In practice, however, researcher-led scholarship may eventually run up against fundamental limitations, since situated knowers presumably have unique access to some kinds of situated knowledge. 10 In that respect, the participatory action model of research that has been recommended and practiced by several policing scholars (e.g., Goldstein 1990;Bradley et al 2006;Wood et al 2007;Wuestewald and Steinheider 2007) holds considerable promise as a model of research for the front lines.…”
Section: Resultsmentioning
confidence: 97%